-7(5x-9)=27-4x

Simple and best practice solution for -7(5x-9)=27-4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(5x-9)=27-4x equation:


Simplifying
-7(5x + -9) = 27 + -4x

Reorder the terms:
-7(-9 + 5x) = 27 + -4x
(-9 * -7 + 5x * -7) = 27 + -4x
(63 + -35x) = 27 + -4x

Solving
63 + -35x = 27 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
63 + -35x + 4x = 27 + -4x + 4x

Combine like terms: -35x + 4x = -31x
63 + -31x = 27 + -4x + 4x

Combine like terms: -4x + 4x = 0
63 + -31x = 27 + 0
63 + -31x = 27

Add '-63' to each side of the equation.
63 + -63 + -31x = 27 + -63

Combine like terms: 63 + -63 = 0
0 + -31x = 27 + -63
-31x = 27 + -63

Combine like terms: 27 + -63 = -36
-31x = -36

Divide each side by '-31'.
x = 1.161290323

Simplifying
x = 1.161290323

See similar equations:

| 2/3x+7=28 | | 6x-(5x+4)=5x-24 | | x^2-10x+23= | | z-29=-35 | | -5n+14=-4n-16 | | -1(6x-2y)=-1(50) | | 4X+1/3=11 | | -2-2/3-3/5 | | x=0-4(7)(-3) | | 3/5(d/8+1/4)=9/16 | | 2x-13x(4-1)=-46 | | 3/8-1/2(3/4)^2 | | p=a+b-3 | | 10x+20=14x | | 2x-3x(4-x)=-46 | | 1/2(5/6)^2+2/9 | | 4y-3(y-4)+4=7 | | -2(-x+y)=-2(-5) | | .5x+.5x=1x+1 | | 40-(3c+4)=5c+20 | | 5x-(2x+3)=6 | | 3/7-(1/2)^3 | | n/7+2=4 | | 41/5=15-(2t+3) | | 3w+9/5-9w+9/2=-30 | | 4x-27=-39+8x | | 1/2(-6+2p) | | 7/9+1/2(5/6)^2 | | (8x^2)/(8x^2+16x) | | -4b+5=2-8b-3b-11 | | 7z+1-5z=8+z-1 | | 4-5x=-8x+1 |

Equations solver categories